Politicised Public Service and Corruption in Lesotho (The Strategic Review for Southern Africa, 2020)
Countries across the world are faced with high levels of corruption. In an effort to combat the threat, governments have declared war on corruption and have consequently put in place some anti-corruption institutions. The causes of corruption are numerous and the consequences are devastating for the social, political and economic development of nations. The perpetrators of corruption are in most cases the public servants as they are charged with the day-to-day administration of the government. This means that the caliber of public servants; which is determined by their recruitment inter alia will influence their practices and conduct. Lesotho has adopted a Westminster model of public administration in which recruitment to the public service is supposed to be merit-based. However, the recruitment of top officers such as Principal Secretaries is politically motivated and this has consequently resulted into a highly politicised public service; literature points that there is a relationship between politicisation of the public service and corruption. In this paper, I scrutinize and explain the effect of a politicised public service on the high magnitude of corruption in Lesotho. This study is based on secondary data such as official government reports, newspapers and research reports. I argue that the highly politicised public service in Lesotho contributes to the corruptionscourge that is besieging the country. I therefore recommend administrative reforms in view of depoliticizing the public service by removing the authority to appoint, promote and dismiss high-ranking public officers from the Prime Minister to a special Parliamentary committee that is inclusive of members from the ruling and opposition parties.